Teacher education reform in Thailand: A semiotic analysis of pre-service English teachers’ perceptions - Jariya Sairattanain (Universiti Pendidikan Sultan Idris, 2021)
The teacher education program in Thailand has undergone various reforms, with the latest being the shortening of the teacher education curriculum from five years to four. To date, very few studies have accounted for this reform. To address this gap, our study sought to analyse pre-service English teachers’ perceptions towards the reform. This was done through a semiotic analysis of visuals contributed by the pre-service teachers. There were a total of 43 visual contributions, which were analysed through Labbo’s typology of symbolisms and attributes discerned from the visuals and their corresponding captions. We were able to categorize the visuals to three types of symbolisms, which were transformative, typographic, and the third type being a combination of the first and second. The most common attribute was positive affect (emotion), with a few visuals rationalizing or questioning the reform. The analysis revealed that the pre-service teachers did not really understand the nature of the reform, despite their positive perception towards change.